Development of Smart Kiddo Games as an Effort to Improve Physical Motor and Language Abilities in Early Childhood - Linda Dwiyanti; Epritha Kurnia Wati; Ayu Titis Rukmana Sari; M. Anis Zawawi; Sita Aulia Rahma (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Sensitive period is when children quickly learn and build mindsets through experiences. This research aims to develop Smart Kiddo Games as an Effort to Improve Physical Motor and Language Ability in Early Childhood. This research is Research and Development using the approaching model developed by Borg & Gall. Starting with a preliminary study, planning, and game product development, continued to the product validation stage (game model) by two material expert validators and two game experts. Product validity analysis using the Aiken formula. Based on the results of the validity test of the assessment instrument by material experts and game experts, all showed results ≥ 0.05 (valid). Thus, it can be concluded that Smart Kiddo Games are appropriate for use in learning as an effort to improve the physical motoric and language abilities of early childhood. Furthermore, it is hoped that it can become one of the most effective and enjoyable early childhood learning strategies, according to the principles and stages of early childhood development.